Managing future oil revenue in Uganda for agricultural development and poverty reduction: A CGE analysis of challenges and options - Wiebelt, Manfred; Pauw, Karl; Matovu, John Mary; Twimukye, Evarist; Benson, Todd (International Food Policy Research Institute, 2011)
With the recent discovery of crude oil reserves along the Albertine Rift, Uganda is set to establish itself as an oil producer in the coming decade. Total oil reserves are believed to be two billion barrels, with recoverable reserves estimated at 0.8-1.2 billion barrels. At peak production, likely to be reached by 2017, oil output will range from 120,000 to 210,000 barrels per day, with a production period spanning up to 30 years. Depending on the exact production levels, the extraction period, the future oil price, and revenue sharing agreements with oil producers, the Ugandan government is set to earn revenue equal to 10-15 percent of GDP at peak production. The discovery of crude oil therefore has the potential to provide significant stimulus to the Ugandan economy and address its development objectives. However, this is subject to careful management of oil revenues to avoid the potential pitfall of a sudden influx of foreign exchange. Dominating the concerns is the potential appreciation in the real exchange rate and subsequent loss of competitiveness in the nonresource tradable goods sectors such as agriculture or manufacturing (Dutch Disease). These sectors are often major employers in developing countries and the engines of growth. Several mitigation measures can be employed by government to counter Dutch Disease, including measures that directly counter the real exchange rate appreciation or measures that offer direct support to traditional export sectors in the form of subsidies.